Non-Glycosylated SARS-CoV-2 Omicron BA.5 Receptor Binding Domain (RBD) with a Native-like Conformation Induces a Robust Immune Response with Potent Neutralization in a Mouse Model - Rawiwan Wongnak; Subbaian Brindha; Mami Oba; Takahiro Yoshizue; Md. Din Islam; M. Monirul Islam; Hitoshi Takemae; Tetsuya Mizutani; Yutaka Kuroda (Molecules, 2024)
The Omicron BA.5 variant of SARS-CoV-2 is known for its high transmissibility and its capacity to evade immunity provided by vaccine protection against the (original) Wuhan strain. In our prior research, we successfully produced the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein in an E. coli expression system. Extensive biophysical characterization indicated that, even without glycosylation, the RBD maintained native-like conformational and biophysical properties. The current study explores the immunogenicity and neutralization capacity of the E. coli-expressed Omicron BA.5 RBD using a mouse model. Administration of three doses of the RBD without any adjuvant elicited high titer antisera of up to 7.3 × 105 and up to 1.6 × 106 after a booster shot. Immunization with RBD notably enhanced the population of CD44+CD62L+ T cells, indicating the generation of T cell memory. The in vitro assays demonstrated the antisera’s protective efficacy through significant inhibition of the interaction between SARS-CoV-2 and its human receptor, ACE2, and through potent neutralization of a pseudovirus. These findings underscore the potential of our E. coli-expressed RBD as a viable vaccine candidate against the Omicron variant of SARS-CoV-2.